Optimalisasi Manajemen Risiko Operasional di Perusahaan Alat Tulis melalui Pendekatan House of Risk - Christabel Priscilla Sihombing; Christian Thomas; Dellyza; Kent Manuel Haryono; Marcia Jocelyn; Riveren Elvina; Safriyana (JURNAL MANAJEMEN RISIKO, 2025)
This study aims to identify operational risks faced by CV BMS, a retail stationery company, and to develop appropriate risk mitigation strategies. The main issue addressed in this research is the high level of competition and the complexity of the supply chain, which may disrupt the company's operational continuity. To address this issue, the House of Risk approach is used, consisting of two phases: the first phase is used to identify and map risk events and agents based on their severity and likelihood, while the second phase is used to formulate effective and efficient risk mitigation strategies. The research was conducted as a case study using survey techniques, both qualitative and quantitative approaches, involving interviews, observations, and the collection of secondary data. The results indicate several key risk agents that significantly contribute to potential operational disruptions, such as supplier delays, demand fluctuations, and human error. The resulting mitigation strategies focus on integrated preventive actions and prioritize measures based on cost-effectiveness and efficiency. The managerial implications of this study highlight the importance of a structured risk management system in supporting the sustainability of company operations amid intense competition in the retail industry.